Multiform-based Baduanjin exercise prevention and treatment for idiopathic pulmonary fibrosis: study protocol for a randomized controlled trial - Zenan Wu; Zehao Hu; Shiwen Ke; Lisha Mo; Mingliang Qiu; Guoshuang Zhu; Wei Zhu; Liangji Liu (BMC, 2023)
Abstract Introduction In this study, we will combine the traditional Baduanjin with Yijin Jing and Wuqinxi to create an optimized Baduanjin exercise program with three different forms (vertical, sitting, and horizontal) to adapt to idiopathic pulmonary fibrosis (IPF) patients in vairous stages of the disease. The purpose of this study is to explore and compare the therapeutic effects of this multi-form Baduanjin, traditional Baduanjin, and resistance training on lung function and limb motor function in IPF patients. The goal of this study is to prove a novel optimal exercise prescription strategy of Baduanjin exercise for improving and protecting lung function in IPF patients. Methods/design A single-blind and randomized controlled trial is used to conduct this study, while the randomization list will be generated using a computerized random number generator and opaque sealed envelopes with group allocation will be prepared. It will be strictly followed to blind the outcome assessors. and until the experiment's conclusion, participants won't know which group they are enrolled in. Patients between the ages of 35 and 80 who have stable diseases and have not regularly practiced Baduanjin exercise in the past will be included. They are divvied up into the following five groups at random: (1) The conventional care group (control group, CG), (2) The traditional Baduanjin exercise group (TG), (3) The modified Baduanjin exercise group (IG), (4) The resistance exercise group (RG) (5) The modified Baduanjin exercise combined with resistance exercise group (IRG). Those CG participants only received the usual treatment, while TC, IG, and RG participants exercised 1 h twice a day for 3 months. MRG participants will have a 3-month intervention with 1 h of Modified Baduanjin Exercise and 1 H of Resistance Training for each day. Every week, all groups underwent will supervis one-day training, with the exception of the control group. The Pulmonary Function Testing (PFT), HRCT, and 6MWT are the main outcome variables. The St. George Respiratory Questionnaire and mMRC are used as secondary outcome measures. Discussion This study may produce a new Baduanjin exercise prescription that is user-friendly, simple to execute, more targeted, and adaptable. Because it consists of three forms, including vertical, sitting, and horizontal, it is more adaptable to the various disease stages and actual situations of IPF patients and may compensate for the shortcomings of conventional pulmonary rehabilitation and traditional Baduanjin. Trial registration Chinese Clinical Trial Registry, ChiCTR2200055559 . Registered on 12 January 2022.